Manipulating overstory density and mineral soil exposure for optimal natural regeneration of Scots pine - Rautio, Pasi; Hallikainen, Ville; Valkonen, Sauli; Karjalainen, Johanna; Puttonen, Pasi; Bergsten, Urban; Winsa, Hans; Hyppönen, Mikko
In northern boreal region the growth of forests is slow, and yield and profit are low, which is why low reforestation costs are important for profitable forestry. If natural regeneration is successful, expensive artificial forest regeneration (planting or direct seeding) can be avoided. In this study, we look at the impact of overstory density and site preparation on natural regeneration and seedling growth of Scots pine. Study stands were established in different parts of Northern Finland and in each stand following treatments: 50, 150 and 250 trees ha−1 or unthinned control, where the stand density was ≥ 250 trees ha−1, were randomly allocated to experimental plots. In addition, site preparation (disc trenching, 4000–5000 m ha−1) was carried out on two experimental plots in which tree density was either 50 or 150 trees ha−1. In the experimental stands seedling number, age and growth were monitored for 11 years. Monitoring revealed that the number of seedlings increased with decreasing tree density. Average seedling height growth was very low or even non-existent in the unthinned control and in the densest (250 trees ha−1) treatment, but increased when the density of trees decreased. The highest seedling number and the highest growth were achieved when the tree density was 50 trees ha−1 and the soil was prepared to expose mineral soil. Achieving e.g. 2000 seedlings ha−1, would need about 40% exposition of mineral soil. The required low tree density implies that not only seed supply from seed trees and site preparation is important for regeneration success in northern boreal Scots pine forests but also the reduction of competition by mature trees. 2023